A relação da etnia Borari com o Igarapé do Jacundá em Alter do Chão Pará - Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
This research focuses on the relationship of the Borari ethnic group with the Jacundá stream in Alter do Chão, justifying the concern with the preservation of the spring to ensure a good amount of water quality for the future of the indigenous community. The theme recalls the issue of the environment, which is of concern, due to the increase in siltation that is occurring around the Jacundá lake, with the deforestation of the headwaters of the stream and the excessive loss of native plants that protect them. With this, the indigenous population that has always had the area as a cultural heritage, where it needs it for its daily consumption, is losing its sacred space. The general objective is to present an environmental and cultural diagnosis for the best way to preserve the area surrounding the Jacundá headwaters. As specific objectives, it is intended to verify the current forms of sociocultural and environmental use of the researched area; analyze the form of usufruct to preserve the area surrounding the Jacundá stream; present an environmental survey as an important factor to find ways to implement laws that protect the surroundings of the area; and contribute to the improvement of public policies at the local, regional and national levels, as a tool for responsible use. For the indigenous people of Alter do Chão, water is a sacred element that needs to be protected, the care of the streams is beyond a simple place for lasers, it is linked to a place of respect for protecting beings. Stop these indigenous people, water is essential for all living beings on earth and its preservation is responsible for the life of plants, animals and people. What makes us think that the preservation of the Jacundá stream is a respect for the ancestors, who left for their survival, both bodily and spiritual.
Keywords: Conservação ambiental; Etnia Borari; Igarapé; Espaço Sagrado; CNPQ:: Ciências Biológicas